2014
DOI: 10.1021/ic501787m
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Induced Change in the Ligand Coordination Mode

Abstract: The reaction of cobalt(II) pivalate with a spin-labeled Schiff base (HL(1)) in organic solvents formed trinuclear complex [Co3(Piv)2L(1)2L(2)2]·Solv (Solv is Me2CO and/or C7H16 and CH3CN) containing both nitroxide L(1) and the product of its single-electron reduction, nitrone L(2). The formation of [Co3(Piv)2L(1)2L(2)2] was a consequence of an unusual phenomenon, which we called "redox-induced change in the ligand coordination mode". A reduction of L(1) to L(2) led to a change in the set of donor atoms and eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In [Co5(Piv)4L were never recorded. This is fully consistent with the data of [23][24][25][26][27], where the authors also used the metals capable of changing the oxidation level.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In [Co5(Piv)4L were never recorded. This is fully consistent with the data of [23][24][25][26][27], where the authors also used the metals capable of changing the oxidation level.…”
Section: Resultssupporting
confidence: 89%
“…An interesting manganese(II)-nitroxide-hydroxylamine complex was known, as well [36]. In the case of the interaction of transition metal compounds with L 2 [23] and of Co(II) pivalate with L 1 , we found that heterospin complexes could be obtained, which contained both the starting nitroxide and the product of its reduction as a result of the transition metal-catalyzed transformation of the starting radical.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…In this reaction, some molecules of the spin-labeled Schiff base HA 2 were reduced to the amidine oxide 4-nitro-2-(4,4,5,5-tetramethyl-3-oxy-4,5-dihydro-1 H -imidazol-2-yl)­phenol (HA 3 ), and the solid product was the [Co 3 (A 2 ) 2 (A 3 ) 2 (Piv) 2 ] mixed-ligand complex containing both the starting imino nitroxide and its reduced diamagnetic analogue. The redox process provoked a change not only in the electronic state of the ligand but also in its coordination mode . If the diamagnetic HA 3 is replaced by the structurally related nitronyl nitroxide HA 1 , we can obtain [Co 3 (A 1 ) 2 (A 2 ) 2 (Piv) 2 ], whose nontrivial peculiarity is the presence of the two paramagnetic ligands in the coordination sphere: nitronyl nitroxide A 1 and imino nitroxide A 2 …”
Section: Introductionmentioning
confidence: 99%